If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -46 = 4x + 76 Reorder the terms: -46 + 6x = 4x + 76 Reorder the terms: -46 + 6x = 76 + 4x Solving -46 + 6x = 76 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -46 + 6x + -4x = 76 + 4x + -4x Combine like terms: 6x + -4x = 2x -46 + 2x = 76 + 4x + -4x Combine like terms: 4x + -4x = 0 -46 + 2x = 76 + 0 -46 + 2x = 76 Add '46' to each side of the equation. -46 + 46 + 2x = 76 + 46 Combine like terms: -46 + 46 = 0 0 + 2x = 76 + 46 2x = 76 + 46 Combine like terms: 76 + 46 = 122 2x = 122 Divide each side by '2'. x = 61 Simplifying x = 61
| 19+1=20 | | 1600=-4x | | 6x+2+3x=74 | | x^4+5x^3+7x^2-4=0 | | -5(6b-8)=30-9b | | f(x)=-2x^3-4x^2-1 | | 7y/10-18=7/17/40 | | -8n-7n=29 | | -4(5+8y)=-17 | | 18x-10+9xz-5z=0 | | -34=-6a+8a | | 0=1.5x^2-4x | | 6x+5ab=7x-9ab | | -9c-5-3c=-32 | | 2(2y+7)=46 | | 2x^2-66=6 | | 2s^2-7s+3=0 | | 49b^2-256=0 | | 3p+5q=-26 | | 3a-(9-7a)=34 | | (18-7n)+1=-9 | | 3x^2(x^2-7)-x^3(2x)=0 | | -7+4(1+8v)=35 | | -8(9k-7)=17 | | (-3x^3y/9y^2z)^-2 | | 8x+7+4x+43=180 | | 4(2x+6)-3=13x+21-5x | | 30=-5+16+3n | | -4=8-4w | | 5f-9+3=-35 | | 3x^2(x^2-7)=0 | | -81+3x=29-2x |